Hormonal contraceptives do not influence concussion recovery in collegiate athletes: Data from the NCAA-DoD CARE Consortium - Kay, J. J. M.; Mangold, K. I.; Lopointe, A.; McAllister, T. W.; Arent, S. M.; McCrea, M.; Broglio, S. P.; Torres-McGehee, T.; Moore, R. D. (Medicine & Science in Sports & Exercise, 2023)
Introduction The hormonal withdrawal hypothesis suggests that progesterone reduction in women after concussion may lead to greater symptom burden and longer recoveries. Current evidence indicates that hormonal stability after head injury may be an important moderator of postconcussive recovery. Thus, female athletes using hormonal contraceptives (HC) may exhibit better recovery profiles as their hormone levels are artificially stabilized. Our investigation sought to examine the relation between HC use and concussion outcomes in female student-athletes.